WET TREATMENT AND THE BEHAVIOR OF ELECTROLESS Ni-P DEPOSITION AT 40 °C ON POLISHED ALUMINA - Alexander Flacker; Cristina B. Adamo; Salomão M. da Silva Junior; Michele O. Silva; Melissa Mederos; Ricardo C. Teixeira (Química Nova, 2023)
The morphology and adhesion strength of the autocatalytic electroless nickel phosphorus (Ni-P) film, deposited at 40 ºC on polished alumina (Al2O3 99.6%) substrate, pretreated by sulfur/nitric solution, sensitizing with acid stannous chloride and activated using palladium chloride solutions, was studied using contact angle (CA), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), mechanical profilometer (DekTak), and direct laser writer (“maskless lithography”). The results showed that after treatment of the polished Al2O3 substrate, it presented a high performance in the electroless deposition of Ni-P thin-film at low temperature (40 ºC). It was obtained a more compact and continuous film, with small grain size and strong adherence.